Remaining Service Life Discharge Conveyor E pada Tambang Batubara di PT XYZ Kabupaten Bungo, Provinsi Jambi - Sandy Renaldi; Elfida Moralista; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyor is a tool that is applied to the mining industry as a tool that supports the process of moving excavated materials such as coal. The structure of the conveyor is made of steel which is subject to corrosion. The disadvantage of corrosion is that it results in a reduction in the thickness of the conveyor structure. Therefore, it is necessary to control and monitor corrosion on the conveyor structure to be observed, so that corrosion can be controlled. The purpose of this research is to determine the type of corrosion, corrosion rate, remaining service life, and control methods. The methodology used in this research is measuring the thickness reduction of the conveyor structure. This research was conducted on a 128 meter long conveyor structure above ground level. Measurement of the thickness of the conveyor structure using the Ultrasonic Thickness Gauge TT 130 at 32 test points. The environmental conditions in the research area are the air temperature in the range of 24,5°C – 26,1°C, while the rainfall ranges from 5,76 mm/year - 7,88 mm/ year. The type of corrosion that occurs in the conveyor structure is uniform corrosion. In controlling this corrosion using a coating method with Seaguard 5000 primer coating, Sherglass FF intermediate coating, and aliphatic acrylic modified polyurethane top coating. The corrosion rate of the conveyor structure ranges from 0.17 - 0.30 mm/year which is included in the good category based on the relative corrosion resistance of steel. Meanwhile, the remaining service life of the conveyor structure ranges from 7,24 - 9,63 years. The service life of the conveyor structure is 8 years, while the design life is 15 years. So it is predicted that 100% can reach its the design life. Abstrak. Conveyor adalah alat yang diaplikasikan pada industri pertambangan sebagai alat yang menunjang dalam proses pemindahan material bahan galian contohnya batubara. Struktur conveyor terbuat dari baja karbon yang dapat mengalami korosi. Kerugian terjadinya korosi yaitu mengakibatkan pengurangan ketebalan struktur conveyor. Oleh karena itu, perlu dilakukannya pengendalian serta monitoring korosi pada struktur conveyor, sehingga korosi dapat dikendalikan. Tujuan dilakukannya penelitian ini untuk mengetahui jenis korosi, laju korosi, sisa umur pakai, dan metoda pengendaliannya. Metodologi yang digunakan dalam penelitian ini yaitu pengukuran pengurangan ketebalan struktur conveyor. Penelitian ini dilakukan pada struktur conveyor sepanjang 128 meter yang berada di atas permukaan tanah. Pengukuran ketebalan struktur conveyor menggunakan alat Ultrasonic Thickness Gauge TT 130 pada 32 test point. Kondisi lingkungan di daerah penelitian yaitu temperatur udara kisaran 24,5°C - 26,1°C, sedangkan curah hujan kisaran 5,76 mm/tahun - 7,88 mm/tahun Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Dalam pengendalian korosi ini menggunakan metoda coating dengan primer coating Seaguard 5000, intermediate coating Sherglass FF, dan top coating aliphatic acrylic modified polyurethane. Laju korosi struktur conveyor berkisar antara 0,17 - 0,30 mm/tahun termasuk ke dalam kategori good berdasarkan ketahanan korosi relatif baja. Sedangkan sisa umur pakai struktur conveyor berkisar antara 7,24 - 9,63 tahun. Umur pakai struktur conveyor yaitu 8 tahun, sedangkan umur desainnya 15 tahun. Sehingga diprediksi sebesar 100% dapat mencapai umur desainnya.